Multi-modal opportunities with digital tools: the example of narrated photographs - Crook, K.M.; Crook, Charles (Springer Science+Business Media, 2016)
This paper explores recent encouragement to cultivate in students a sensitivity towards the ‘multi-modal’ nature of human communication. We consider what this means for educational practice and, in particular, how such an imperative might be addressed with digital tools. In discussing these issues, a neglected format for multimodal digital expression will be introduced: namely, narrated images or ‘sound photos’. Observations on multimodal expression are then offered as they were prompted from an intervention requiring students to create such artefacts with digital tools. Taken together, these observations highlight both the potential of extending multi-modality more firmly into the curriculum but also the challenges that can arise from doing so. The paper starts with an outline of what is entailed in the concept of ‘multi-modality’. It then considers how digital tools relate to this notion, and the format of a narrated photograph is introduced. A practical exercise within the realm of mobile learning is described and its implications for addressing issues of visual literacy and oracy are discussed.